Non-autonomous Cellular Responses to Ototoxic Drug-Induced Stress and Death - Francis, Shimon P.; Cunningham, Lisa L. (Frontiers in Cellular Neuroscience, 2017)
The first major recognition of drug-induced hearing loss can be traced back more than seven decades to the development of streptomycin as an antimicrobial agent. Since then at least 130 therapeutic drugs have been recognized as having ototoxic side- effects. Two important classes of ototoxic drugs are the aminoglycoside antibiotics and the antineoplastic agent cisplatin. These drugs save the lives of millions of people worldwide, but they also cause irreparable hearing loss. In the inner ear, sensory hair cells (HCs) and spiral ganglion neurons (SGNs) are important cellular targets of these drugs, and most mechanistic studies have focused on the cell-autonomous responses of these cell types in response to ototoxic stress. Despite several decades of studies on ototoxicity, important unanswered questions remain, including the cellular and molecular mechanisms that determine whether HCs and SGNs will live or die when confronted with ototoxic challenge. Emerging evidence indicates that other cell types in the inner ear can act as mediators of survival or death of sensory cells and spiral ganglion neurons. For example, glia-like supporting cells (SCs) can promote survival of both HCs and SGNs. Alternatively, SCs can act to promote HC death and inhibit neural fiber expansion. Similarly, tissue resident macrophages activate either pro-survival or pro-death signaling that can influence HC survival after exposure to ototoxic agents. Together these data indicate that autonomous responses that occur within a stressed HC or SGN are not the only (and possibly not the primary) determinants of whether the stressed cell ultimately lives or dies. Instead non-autonomous cellular responses are emerging as significant determinants of HC and SGN survival vs. death in the face of ototoxic stress. The goal of this review is to summarize the current evidence on non-autonomous cellular responses to ototoxic stress and to discuss ways in which this knowledge may advance the development of therapies to reduce hearing loss caused by these drugs.